Neuroethics of Non-primary Brain Computer Interface: Focus on Potential Military Applications - Munyon, Charles N. (Frontiers in Neuroscience, 2018)
Brain computer interface (BCI) has many potential military applications. This is reflected in the considerable Department of Defense funding available for BCI research. The preponderance of both military and civilian research to date has focused on BCI for restoration of lost motor or sensory function. A more uniquely military emphasis has been on use of EEG-based BCI for augmentation of sensory capabilities or improved control of unmanned or piloted vehicles. Recent technological advances, coupled with an increasingly sophisticated understanding of brain network architecture, have spurred interest in non-primary BCI. Exploration of possible military applications could lead not only to improved survivability of American and allied warfighters, but also to more rapid adoption of restorative technologies on the civilian side due to the accelerating effect that defense funding can have on technological development. Equally important, however, is that pre-emptive ethical examination of these technologies should occur at the same time that research commences on new applications, rather than after they have been explored and refined. This article will focus on conceptual analysis of potential military applications for non-primary BCI within an ethical framework that considers both intended uses and the potential for diversion of the technology to other applications.